Aquatic Exercise Programs for Children and Adolescents with Cerebral Palsy: What Do We Know and Where Do We Go? - J. W. Gorter; S. J. Currie (International Journal of Pediatrics)
Aquatic exercise programs may be a beneficial form of therapy for children and adolescents with cerebral palsy (CP), particularly for those with significant movement limitations where land-based physical activity is difficult. The most recently published systematic review (2005) on aquatic interventions in children with CP found supportive but insufficient evidence on its effectiveness. The aim of this paper is to review recently published literature since 2005 with a focus on aquatic exercise for children with CP. In total, six new studies were published with a main focus on aerobic aquatic interventions in higher functioning children and adolescents with CP. Swimming is one of the most frequently reported physical activities in children and adolescents with CP. Therefore, information on its safety and benefits is highly needed, for those with more severe CP in particular. Research design issues are discussed to help guide future research and practice.